The effectiveness of DNA methylation in determining age estimation from biological samples at the crime scene - Tezel, Ayşen; Kılıçaslan, Duygu Yavuz (The Bulletin of Legal Medicine, 2025)
DNA methylation is one of the most widely used epigenetic mechanisms in the field of forensic sciences. Today, numerous CpG sites are analyzed for their age-related methylation to estimate chronological age in humans.The aim is to determine age estimation from biological samples obtained at the crime scene. This research will also serve as a foundation for future age estimation studies.Age estimation can be performed from biological samples that can be detected during a forensic investigation. In this regard, a detailed study on forensic age estimation was conducted using the PubMed, Scopus, and Google Scholar databases.CpG sites were studied using the Bisulfite Conversion method in biological samples obtained from male and female volunteers across different age categories to establish their correlation with age. The Mean Absolute Deviation (MAD) or Mean Absolute Error (MAE) values of the estimated age compared to biological and chronological age groups were determined.Age estimations performed with artificial intelligence in blood samples yielded an average MAD value between 3 and 5 years. However, age dependencies according to tissue types were detected, and their accuracy was observed to be lower compared to blood samples. Therefore, in forensic applications, age estimation should be performed based on the type of biological material obtained at the crime scene. As a result of methylation analyses numerous age-related CpG sites are conducted to estimate chronological age in humans.
Keywords: DNA methylation; Age estimation; Biologic samples; Epigenetics; Mean Absolute Deviation; Mean Absolute Error